Porang (Amorphophallus muelleri) Biscuits Fortified with Moringa (Moringa oleifera, Lamk) Leaf Flour on decrease Inflammation in kidney of Obese Wistar Rats (Rattus norvegicus) - Safitri, Nisrina Ulayya; Setyawan, Novan Adi; Pesik, Riza Novierta; Budiani, Dyah Ratna (Smart Medical Journal, 2024)
Introduction: The high incidence of obesity is due to the habit of eating snacks. The habit of eating snacks can be replaced with healthy snacks, one of which is porang biscuits fortified with moringa flour. This study was conducted to determine the effect of intake of porang biscuits fortified with moringa flour on glomerular area and interstitial inflammation of the kidneys of Wistar rats modeled obesity.Methods: Laboratory experimental research with randomized postest control group design. 30 Wistar male rats were divided into 5 groups. The negative control group (KN) was given standard feed, the positive control group (KP) was given high-fat high-fructose feed, the treatment groups (P1, P2, and P3) were given porang biscuits fortified with moringa flour with varying doses of moringa leaf powder 150, 250, and 350 mg/200grBB after induction. Glomerular area was measured with raster image. The results of glomerular area and interstitial inflammation score were analyzed by oneway ANOVA and post hoc Tukey HSD. Correlation of glomerular area and interstitial inflammation score with increasing dose were analyzed by Pearson.Results: There was no significant difference in glomerular area between all groups and no correlation between glomerular area and increasing dose of moringa powder. There were significant differences in interstitial inflammation scores between KN-KP, KN-P1, KN-P2, KN-P3, KP-P3, P1-P3 and P2-KP. The correlation between interstitial inflammation and increasing dose of moringa leaf powder was p=0.000 and r=-0.776Conclusion: There is a difference in the interstitial inflammation score of the kidneys of obese Wistar rats after intake of porang biscuits fortified with Moringa leaf powder at a dose of 350 mg/200 grBB while there is no difference in glomerular area. There is a strong negative correlation between increasing doses of moringa leaf powder and interstitial inflammation.